How did ancient human activities influence the properties and development of soil?—a case study of the Yangshao Village cultural relic site, Henan Province - Zha, Lisi; Wang, Wenjing; Zhong, Junhong; Su, Yiqi; Chang, Dandan (Frontiers in Environmental Science, 2024)
Introduction: What were the effects of paleoanthropogenic activities on the physicochemical properties and degree of the development of soil? To search for this answer, we can not only understand the different types of ancient human activities but also explore the intensity and characteristics of the activities. Methods: In this study, soil samples from different soil layers and two profiles in the Yangshao Village cultural site in Henan Province were collected. Their physicochemical properties and the sporophyte phyllosilicates they contain were analyzed and compared. Results: We found that the paleoanthropogenic activities started in the relatively low-lying area, in which the slash-and-burn activities resulted in the soil being filled with intrusions such as charcoal debris and ceramic shards. At the same time, the coarse-grained matter was affected by the plowing activities and mostly decomposed into fine particles, and the content of clay particles reached an extreme value. The total nitrogen, phosphorus, and calcium carbonate content exceeded the average value of the natural profile, indicating that ancient humans had used human and animal feces to a certain extent to restore the fertility of arable land. Discussion: Overall, ancient human activities hindered the development of the soil, especially the ground created due to habitation activities. From the type and content of clay minerals, it could be seen that the soil in this layer has been transported from other places, has a high content of clay particles, and has experienced fire baking. It was assumed that the ground was used to cover the grain or bury the garbage and lay with clay in order to achieve the effect of sealing. As a result, the soil voids and structure had been damaged to some extent, which prevented the downward leaching or precipitation of soil particles and minerals to a certain extent, thus affecting soil development.